Impact of hierarchical hospital reform on patients with diabetes in China: a retrospective observational analysis - Xu, Junfang (BMJ Open, 2021)
OBJECTIVES: We assess whether China’s diabetes pilot hierarchical diagnosis and treatment reforms shifted patient healthcare-seeking behaviour towards primary health institutions (PHIs) and away from secondary and tertiary hospitals. From the patients’ perspective, we evaluate whether the hierarchical system saw the decline of average hospital cost, out-of-pocket (OOP) expenses and the increase of reimbursement rate in PHIs. From the health system’s perspective, we also assessed whether the share of PHIs in total costs, total visits and reimbursement rate increased and the share of secondary and tertiary hospitals decreased. METHODS: Data were collected from the health insurance bureau of 11 cities in Shandong Province, China between 2015 and 2017, which included 9 118 518 outpatient visits and 622 739 inpatient visits. For both inpatients and outpatients and the health system, we analysed health services-seeking characteristics including hospital costs, hospital visits, OOP expense and reimbursements of hospital costs. Binary logistic regression was conducted to analyse the influencing factors of seeking PHI health services. RESULTS: PHIs remained the lowest hospital cost provider, but average hospital costs declined across all three healthcare levels of PHIs, secondary hospitals and tertiary hospitals from 2015 to 2017. The hierarchical system aimed to shift patients to PHIs, increasing PHIs’ share of total hospital costs. However, the PHI share of total outpatient costs declined 12.0%, while rising 15.0% in secondary hospitals, the opposite of the goal of the hierarchical medical system. Average outpatient visits rose roughly at the same rate in PHIs (5.1%) as secondary hospitals (6.8%), with no evidence of a shift in patient visits between hospital levels over 2015–2017. Average inpatient visits fell across all levels of hospitals, with no significant difference in the rate of decline between PHIs (9.4%) and secondary (7.5%) and tertiary (7.8%) hospitals. For outpatient and inpatient services, the binary logistic regression showed that over the 2015–2017 period patients with diabetes increasingly used higher level hospitals rather than PHIs (p<0.05). The only success of the hierarchical medical system was the relative fall of OOP outpatient expenses, which fell more rapidly in PHIs (13.7%) than secondary (5.0%) and tertiary (3.5%) hospitals. However, inpatient OOP expenses fell only 2.2% for PHIs, less than half that of secondary (5.5%) and tertiary (7.4%) hospitals, the opposite of the aim of the hierarchical system reform. CONCLUSIONS: The implementation of the hierarchical medical system for patients with diabetes did not achieve its goal of increasing PHI utilisation and decreasing secondary and tertiary hospital utilisation. Enhancing the utilisation of PHIs for diabetes and other patients requires further health reform, including educating patients on PHI use, further reforming the health insurance schemes, improving PHI facilities and encouraging referrals to PHIs from higher level hospitals.